EXPLORING STAKEHOLDERS’ PERCEPTIONS OF THE GREEN CAMPUS INITIATIVE IN SOUTH AFRICAN HIGHER EDUCATION INSTITUTIONS - Katleho Nolwandle MAFONGOSI; Bankole Osita AWUZIE; Alfred Atsango TALUKHABA (Journal of Construction Project Management and Innovation)
Although mixed performances have been documented in attempts by South African higher education institutions (HEIs) to integrate the ethos of sustainable development (SD) into their core activities, neglect of such integration in the management of built assets and spaces on their campuses has been observed. This prompted the introduction of the Green Campus Initiative (GCI) in South Africa in 2012, among other things. However, implementation performance of the GCI seems to be under-reported, hence the need for this study. The study explored the level of awareness, as well as the perceptions of stakeholders, of the success or otherwise of the GCI in their respective institutions. Adopting a case study research design, this study relied on semi-structured interviews. Interviewees were recruited through purposive snowballing at a selected HEI, which served as a case study. Data that accrued from these sources was analysed using the thematic analysis technique. The preliminary findings revealed a considerable level of awareness among the interviewed stakeholders. The interviewees also agreed regarding the potential of the concept to make a significant contribution to resolving the environmental challenges bedevilling the South African context. Impediments hindering successful implementation of the initiative were also identified. Findings from this study will contribute to a wider research project seeking to optimise GCI implementation performance in South African HEIs.